DNMT3A moderates cognitive decline in subjects with mild cognitive impairment: replicated evidence from two mild cognitive impairment cohorts. (June 2015) - Chouliaras, Leonidas; Kenis, Gunter; Visser, Pieter Jelle; Scheltens, Philip; Tsolaki, Magda; Jones, Roy W; Kehoe, Patrick G; Graff, Caroline; Girtler, Nicola G; Wallin, Åsa K; Rikkert, Marcel Olde; Spiru, Luiza; et al.
Epigenetic dysregulation has been associated with cognitive decline and Alzheimer's disease. The present study investigated associations between common SNPs in genes regulating DNA methylation and age-related changes in cognitive decline in two independent prospective cohorts of patients suffering from mild cognitive impairment. An association between the rs1187120 SNP in DNMT3A and annual decline in cognitive functioning was discovered and replicated, suggesting that DNMT3A moderates cognitive decline in subjects with mild cognitive impairment.